Lead-free piezoelectric composition and piezoelectric element
By introducing the secondary phase of Mn-Ti-O-based oxide into the lead-free piezoelectric composition and controlling its particle size distribution, the problem of low dielectric breakdown voltage of the existing lead-free piezoelectric composition is solved, and the effect of excellent piezoelectric characteristics and insulation is achieved.
Patent Information
- Application Number
- CN202380055206.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lead-free piezoelectric composition has excellent piezoelectric properties, but has low dielectric breakdown voltage and has problems with insulation.
The lead-free piezoelectric composition is adopted which includes the main phase of the alkaline niobate perovskite oxide and the sub-phase of the Mn-Ti-O-based oxide. The maximum particle size and the cumulative 80% particle size of the secondary phase are controlled at 35 μm or less, and the average particle size is preferably 24 μm or less.
A lead-free piezoelectric composition with excellent piezoelectric characteristics and excellent insulation is achieved, and the dielectric breakdown voltage is significantly improved, ensuring the efficient performance of the composition.
Smart Images

Figure CN119604477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lead-free piezoelectric composition and a piezoelectric element. Background Art
[0002] In the past, many piezoelectric elements were made of PZT (lead zirconate titanate)-based materials. However, the lead component contained in PZT is considered a problem because it causes environmental load. In recent years, the development of piezoelectric elements made of lead-free materials that do not contain lead has been promoted.
[0003] As such a lead-free material, for example, a lead-free piezoelectric composition has been proposed, which comprises: a main phase formed by a first crystal phase formed by an alkali niobate perovskite-type oxide, and a subphase comprising a second crystal formed by an M-Ti-O spinel compound (the element M is an element having a valence of 1 to 4) (see patent document 1).
[0004] The alkali niobate perovskite oxide constituting the main phase is a material that is prone to forming voids that cause a decrease in piezoelectric properties, but the voids in the main phase are filled with a subphase containing a second crystal, thereby stabilizing the structure of the main phase (first crystal phase). Therefore, the lead-free piezoelectric composition has excellent piezoelectric properties. That is, if a force is applied to the lead-free piezoelectric composition, a voltage is generated, and if a voltage is applied, the size of the lead-free piezoelectric composition is expanded or contracted, and the shape is changed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5715309 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] The lead-free piezoelectric composition has excellent piezoelectric properties, but has a low dielectric breakdown voltage and has problems with insulation properties.
[0010] Solutions for solving problems
[0011] An object of the present invention is to provide a lead-free piezoelectric composition having excellent piezoelectric characteristics and excellent insulating properties.
[0012] The solution for solving the above-mentioned problems is as follows.
[0013] <1> A lead-free piezoelectric composition comprising: a main phase comprising an alkali niobate perovskite-type oxide, and a subphase comprising a Mn-Ti-O-based oxide, wherein the maximum particle size of the Mn-Ti-O-based oxide in the subphase is less than 35 μm and the cumulative 80% particle size (D80) based on number is less than 32 μm.
[0014] <2> The lead-free piezoelectric composition according to <1>, wherein an average particle size of the Mn—Ti—O-based oxide in the subphase is 24 μm or less.
[0015] <3> The lead-free piezoelectric composition according to <1> or <2>, wherein the Mn—Ti—O-based oxide includes MnTi 2 O 4 or Mn 2 TiO 4 .
[0016] <4> A piezoelectric element comprising a laminate of a piezoelectric ceramic layer formed from the lead-free piezoelectric composition according to any one of <1> to <3> and an electrode mounted on the piezoelectric ceramic layer.
[0017] Effects of the Invention
[0018] According to the present invention, a lead-free piezoelectric composition having excellent piezoelectric characteristics and excellent insulating properties can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A perspective view of a piezoelectric element according to Embodiment 1
[0020] Figure 2 A cross-sectional view of a piezoelectric element according to Embodiment 2 DETAILED DESCRIPTION
[0021] Hereinafter, the lead-free piezoelectric composition and the piezoelectric element according to the embodiment will be described.
[0022] The lead-free piezoelectric composition has a main phase including an alkali niobate perovskite-type oxide and a subphase including a Mn—Ti—O-based oxide.
[0023] The main phase is formed of a first crystal phase including an alkali niobate perovskite-type oxide. The alkali niobate perovskite-type oxide is represented by the following composition formula (1).
[0024] (A1 a M1 b ) c (Nb d1 Mn d2 Ti d3 Zr d4 ) 3+e ···(1)
[0025] The element A1 is at least one of the alkali metals Li, Na, and K. The element M1 is at least one of the alkaline earth metals Ba (barium), Ca (calcium), and Sr (strontium).
[0026] In the above compositional formula (1), element A1 and element M1 are disposed at the A-site of the perovskite structure, and Nb (niobium), Mn (manganese), Ti (titanium), and Zr (zirconium) are disposed at the B-site.
[0027] As the values of coefficients a to e in the above compositional formula (1), values are selected that are within the values for which the perovskite structure is formed and are preferable from the viewpoint of the electrical properties or piezoelectric properties (particularly the piezoelectric constant d 33 ) of the lead-free piezoelectric composition.
[0028] Specifically, coefficients a and b satisfy 0 < a < 1, 0 < b < 1, and a + b = 1, excluding a = 0 (i.e., a composition containing no alkali metal) and b = 0 (i.e., a composition containing neither Ba, Ca, nor Sr).
[0029] Coefficient c with respect to the entire A-site satisfies 0.80 < c < 1.10, preferably 0.84 ≤ c ≤ 1.08, and more preferably 0.88 ≤ c ≤ 1.07.
[0030] Coefficients d1, d2, d3, and d4 satisfy 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, 0 ≤ d4 < 1, and d1 + d2 + d3 + d4 = 1. Exclude d1 = 0 (a composition containing no Nb), d2 = 0 (a composition containing no Mn), and d3 = 0 (a composition containing no Ti). The coefficient d4 of Zr can be zero (i.e., it can be a composition containing no Zr).
[0031] In the coefficient 3 + e of oxygen, coefficient e is a positive or negative value representing the deficiency or excess of oxygen with respect to the coefficient of oxygen, which is usually 3. The coefficient 3 + e of oxygen can take values for forming a perovskite-type oxide as the main phase. A typical value of coefficient e is e = 0, preferably 0 ≤ e ≤ 0.1. It should be noted that the value of coefficient e can be calculated from the electrical neutrality condition of the composition of the main phase. Among them, as the composition of the main phase, a composition slightly deviating from the electrical neutrality condition is also allowed.
[0032] Among the alkali niobate perovskite-type oxides represented by the above compositional formula (1), oxides having K, Na, and Nb as main metal components are called "KNN" or "KNN materials" and have excellent piezoelectric properties, electrical properties, etc.
[0033] It should be noted that the above compositional formula (1) can be rewritten by substituting with the following compositional formula (1A).
[0034] (K a1 Na a2 Li a3 Ca b1 Sr b2 Ba b3 ) c (Nb d1 Mn d2 Tid3 Zr d4 )O 3+e ···(1A)
[0035] The above compositional formula (1) is equivalent to the compositional formula (1A), which is a1 + a2 + a3 = a and b1 + b2 + b3 = b. The coefficient a1 of K is 0 < a1 ≤ 0.6, the coefficient a2 of Na is 0 < a1 ≤ 0.6, and the coefficient a3 of Li is 0 ≤ a3 ≤ 0.2 (preferably 0 ≤ a3 ≤ 0.1).
[0036] The secondary phase is formed by the second crystal phase containing an Mn-Ti-O system oxide. The Mn-Ti-O system oxide is an oxide containing Mn (manganese) and Ti (titanium), and is represented, for example, by the following compositional formula (2).
[0037] MnTiO y ···(2)
[0038] The coefficient y satisfies 2 ≤ y ≤ 8.
[0039] In addition, as the Mn-Ti-O system oxide, it may be MnTi2O4.
[0040] In addition, as the Mn-Ti-O system oxide, it may be Mn2TiO4.
[0041] It should be noted that the composition of M and Ti in the Mn-Ti-O system oxide (such as MnTi2O4, Mn2TiO4) can deviate from the desired value within the range of ±0.2.
[0042] The lead-free piezoelectric composition of the present embodiment may contain other crystal phases (such as the third crystal phase, etc.) other than the second crystal phase as long as the object of the present invention is not impaired.
[0043] In the lead-free piezoelectric composition of the present embodiment, the maximum particle size of the Mn-Ti-O system oxide in the secondary phase is 35 μm or less. The method for measuring the maximum particle size of the Mn-Ti-O system oxide will be described later.
[0044] In addition, in the lead-free piezoelectric composition of the present embodiment, the cumulative 80% particle size (D80) based on the number of the Mn-Ti-O system oxides in the secondary phase is 32 μm or less. The method for measuring the cumulative 80% particle size (D80) based on the number will be described later.
[0045] If the maximum particle size of the Mn-Ti-O system oxide in the secondary phase and the cumulative 80% particle size (D80) based on the number of the Mn-Ti-O system oxides in the secondary phase are respectively within the above ranges, a lead-free piezoelectric composition with excellent piezoelectric properties and excellent insulation properties (that is, a high dielectric breakdown voltage) can be obtained.
[0046] In the lead-free piezoelectric composition of the present embodiment, the average particle size of the Mn-Ti-O-based oxide in the subphase is preferably 24 μm or less. The method for measuring the average particle size of the Mn-Ti-O-based oxide will be described later.
[0047] When the average particle size of the Mn—Ti—O-based oxide in the subphase is within the above range, the piezoelectric characteristics and insulating properties of the lead-free piezoelectric composition can be easily improved.
[0048] The subphase including the second crystal phase satisfying the above conditions is dispersed and arranged in the main phase formed by the first crystal phase in a scattered point shape. The subphase fills the pores (voids) formed between the fine crystals of the main phase. The subphase does not have piezoelectric properties, but it is mixed with the main phase to improve the sintering property and structural stability of the lead-free piezoelectric composition, and improve the insulation property.
[0049] In addition, in the present embodiment, the ratio of the subphase contained in the lead-free piezoelectric composition is not particularly limited unless the purpose of the present invention is impaired, and is preferably, for example, 0.5% by volume or more and 5% by volume or less.
[0050] Next, refer to Figure 1 At the same time, the piezoelectric element 200 according to the first embodiment will be described. Figure 1 FIG. 2 is a perspective view of a piezoelectric element 200 according to Embodiment 1. Figure 1 As shown, the appearance is a disk, and it has: a disk-shaped piezoelectric layer (an example of a piezoelectric ceramic layer) 100, and electrodes 301 and 302 mounted on the upper surface and the lower surface of the piezoelectric layer 100. The piezoelectric layer 100 is formed of the above-mentioned lead-free piezoelectric composition. The piezoelectric layer 100 is polarized in the thickness direction. The electrodes 301 and 302 are formed of Au, for example.
[0051] Here, an example of a method for manufacturing the piezoelectric element 200 of embodiment 1 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.
[0052] In addition, a variety of raw material powders required for forming the secondary phase are prepared, and these raw material powders are weighed in a manner to obtain the target composition. The raw material powders may be oxides of the elements contained in the secondary phase, carbonates of the elements, hydroxides of the elements, etc. For the mixture of the weighed raw material powders, ethanol is added to the mixture, and wet mixing is preferably performed for more than 15 hours using a ball mill to obtain a slurry. The obtained slurry is dried, and the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery secondary phase pre-baked product.
[0053] Next, a dispersant, a binder and ethanol are added to the obtained pre-baked product of the main phase and the pre-baked product of the sub-phase, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the obtained slurry is dried, and the obtained dried product is suitably granulated, and the obtained product is subjected to uniaxial pressing, for example, under a pressure of 20 MPa, to obtain a disk-shaped preform. Then, the preform is subjected to CIP treatment (cold isostatic pressing treatment), for example, under a pressure of 150 MPa, thereby obtaining a molded body.
[0054] Next, the obtained molded body is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment. Then, the molded body after the binder removal treatment is kept at a temperature of 1000 to 1200° C. for 2 to 5 hours and fired in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit, thereby obtaining a piezoelectric layer.
[0055] For example, electrodes made of Au are formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Then, the laminated product with the electrodes formed on the piezoelectric layer is subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50° C., thereby realizing the voltage characteristics of the piezoelectric layer. In this way, the piezoelectric element 200 is obtained.
[0056] It should be noted that, in the lead-free piezoelectric composition used in the voltage element 200, the subphase is formed by the second crystal phase containing the Mn-Ti-O series oxide as described above. The size of the crystal particles in the subphase (maximum particle size, D80, average particle size, etc.) can be controlled to the desired size by appropriately setting the particle size of the subphase pre-baked product and the firing temperature of the molded body after the debindering treatment under a reducing atmosphere. For example, the larger the particle size of the subphase pre-baked product, the larger the crystal particles of the subphase of the lead-free piezoelectric composition finally obtained. In addition, the higher the firing temperature of the molded body after the debindering treatment under a reducing atmosphere, the larger the crystal particles of the subphase of the lead-free piezoelectric composition finally obtained.
[0057] Next, refer to Figure 2At the same time, the piezoelectric element 10 according to the second embodiment will be described. Figure 2 2 is a cross-sectional view of a piezoelectric element 10 according to Embodiment 2. The piezoelectric element 10 of this embodiment is as follows. Figure 2 As shown, it comprises: a piezoelectric layer (an example of a piezoelectric ceramic layer) 11; a plurality of internal electrodes 12, 13 connected to the piezoelectric layer 11; and two external electrodes 14, 15 connected to the internal electrodes 12, 13. The piezoelectric layer 11 is formed of the above-mentioned lead-free piezoelectric composition. The internal electrodes 12, 13 are mainly composed of a base metal (for example, nickel). The piezoelectric layer 11 and the internal electrodes 12, 13 are alternately stacked. More specifically, the piezoelectric layer 11 and the internal electrodes 12, 13 are stacked in the order of piezoelectric layer 11, internal electrode 12, piezoelectric layer 11, internal electrode 13, piezoelectric layer 11, etc., and one piezoelectric layer 11 is sandwiched by two internal electrodes 12, 13. The two external electrodes 14, 15 are arranged on the outer surface of the stack of the piezoelectric layer 11 and the internal electrodes 12, 13. The external electrodes 14, 15 are mainly composed of Au, for example. One end of one of the two internal electrodes 12 and 13 connected to one piezoelectric layer 11 is connected to an external electrode 14, and one end of the other internal electrode 13 is connected to another external electrode 15. By applying a voltage between the external electrodes 14 and 15, the piezoelectric layer 11 expands and contracts, and the piezoelectric element 10 as a whole expands and contracts.
[0058] Here, an example of a method for manufacturing the piezoelectric element 10 of embodiment 2 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.
[0059] In addition, a variety of raw material powders required for forming the secondary phase are prepared, and these raw material powders are weighed in a manner to obtain the target composition. The raw material powders may be oxides of the elements contained in the secondary phase, carbonates of the elements, hydroxides of the elements, etc. For the mixture of the weighed raw material powders, ethanol is added to the mixture, and wet mixing is preferably performed for more than 15 hours using a ball mill to obtain a slurry. The obtained slurry is dried, and the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery secondary phase pre-baked product.
[0060] Next, a dispersant, a binder, and an organic solvent (such as toluene) are added to the obtained pre-baked main phase and the pre-baked sub-phase, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the slurry is processed into a sheet shape using a doctor blade method or the like to produce a ceramic green sheet.
[0061] Next, an electrode layer serving as an internal electrode is formed on one side of the ceramic green sheet using a conductive paste for internal electrodes, for example, by screen printing. The electrode layer mainly contains a base metal, for example, nickel (Ni).
[0062] Then, a plurality of ceramic green sheets with electrode layers formed thereon are stacked in such a manner that the electrode layers are alternately exposed from both sides, and ceramic green sheets without electrode layers are further stacked on both the front and back sides of the obtained stacked body. The obtained stacked body is pressed to obtain a stacked body in which ceramic green sheets and electrode layers are alternately stacked. The stacked body is cut into a desired shape, and then, for example, is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment.
[0063] The binder-removed laminate is sintered for 2 to 5 hours at 1000 to 1200° C. in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reducing side by more than a single digit.
[0064] After the side of the fired laminate is appropriately polished, a pair of external electrodes made of Au are formed on the side of the laminate, for example, by sputtering. The pair of external electrodes are formed in a manner that the laminate is placed therebetween and faces each other. The laminate with the external electrodes formed thereon is subjected to polarization treatment to obtain the piezoelectric element 10.
[0065] It should be noted that, in the lead-free piezoelectric composition used in the voltage element 10, the subphase is formed by the second crystal phase containing the Mn-Ti-O series oxide as described above. The size of the crystal particles in the subphase (maximum particle size, D80, average particle size, etc.) can be controlled to the desired size by appropriately setting the particle size of the subphase pre-baked product and the firing temperature of the molded body after the debindering treatment under a reducing atmosphere. For example, the larger the particle size of the subphase pre-baked product, the larger the crystal particles of the subphase of the lead-free piezoelectric composition finally obtained. In addition, the higher the firing temperature of the molded body after the debindering treatment under a reducing atmosphere, the larger the crystal particles of the subphase of the lead-free piezoelectric composition finally obtained.
[0066] The manufacturing methods of the above-mentioned embodiments 1 and 2 are examples, and various other processes and processing conditions for manufacturing piezoelectric elements can be used. For example, the raw materials can be mixed in a quantitative ratio that meets the composition of the final lead-free piezoelectric composition, and the mixture can be fired instead of pre-generating the pre-baked products of the main phase and the auxiliary phase separately, and then mixing and firing the powders of the two. Among them, according to the method of pre-generating the pre-baked products of the main phase and the auxiliary phase separately and then mixing them, it is easy to more strictly manage the composition of the main phase and the auxiliary phase, so the yield of the lead-free piezoelectric composition can be improved. In addition, as the material of the electrode, metals or alloys such as platinum (Pt), silver palladium (Ag-Pd), and silver (Ag) can also be used.
[0067] The lead-free piezoelectric composition and piezoelectric element disclosed in this specification have excellent piezoelectric properties, high dielectric breakdown voltage, and excellent insulation. Such lead-free piezoelectric composition and piezoelectric element can be widely used for vibration detection, pressure detection, oscillation, piezoelectric device applications, etc. For example, it can be used for sensors for detecting various vibrations (such as Knox sensors and combustion pressure sensors), vibrators, actuators, piezoelectric devices such as filters, high voltage generating devices, micro power sources, various driving devices, position control devices, vibration suppression devices, fluid discharge devices (such as paint discharge and fuel discharge), etc.
[0068] Example
[0069] Hereinafter, the present invention will be described in further detail based on examples. It should be noted that the present invention is not limited to these examples.
[0070] [Examples 1 to 7]
[0071] (Preparation of Main Phase Pre-baked Material)
[0072] As raw material powders, K2CO3 powder, Na2CO3 powder, Nb2O5 powder, TiO2 powder, ZrO2 powder, MnCO3 powder, and BaCO3 powder were prepared, and each of these raw material powders was weighed in such a way that the content (mol%) of each element became the value shown in Table 1. A suitable amount of ethanol was added to the mixture of each weighed raw material powder, and wet mixing was performed for 15 hours using a ball mill to obtain a slurry. The obtained slurry was dried, and after drying, the obtained mixed powder was pre-baked for 1 to 10 hours under an atmospheric atmosphere at a temperature of 600 to 1100° C. to obtain a pre-baked product of the main phase.
[0073] (Production of Subphase Pre-baked Product)
[0074] As raw material powders, MnCO3 powder and TiO2 powder were prepared, and each of these raw material powders was weighed in such a manner as to have the composition (MnTi2O4) shown in Table 2. A suitable amount of ethanol was added to the mixture of each weighed raw material powder, and wet mixing was performed for 15 hours using a ball mill to obtain a slurry. The obtained slurry was dried, and after drying, the obtained mixed powder was pre-baked for 1 to 10 hours under an atmospheric atmosphere at a temperature of 600 to 1100° C. to obtain a subphase pre-baked product.
[0075] (Fabrication of Piezoelectric Components)
[0076] To the obtained main phase pre-baked product and the sub-phase pre-baked product, a dispersant, a binder and ethanol are added, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the obtained slurry is dried, and the obtained dried product is suitably granulated and uniaxially pressed under a pressure of 20 MPa to obtain a disc-shaped preform. Then, the preform is subjected to a CIP treatment (cold isostatic pressing treatment) under a pressure of 150 MPa to obtain a molded body. It should be noted that the mixing ratio of the main phase pre-baked product and the sub-phase pre-baked product is adjusted in such a way that the ratio (volume %) of the main phase to the sub-phase becomes 97:3.
[0077] The obtained molded body is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment. Then, the molded body after the binder removal treatment is kept at a temperature of 1000 to 1200° C. for 2 to 5 hours in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit, and then fired to obtain a piezoelectric layer.
[0078] Electrodes made of Au were formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Afterwards, the laminate with electrodes formed on the piezoelectric layer was subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50°C, thereby reflecting the voltage characteristics of the piezoelectric layer and obtaining the piezoelectric elements of each embodiment.
[0079] In Examples 1 to 7, the particle size of the sub-phase pre-baked product and the firing temperature of the molded body after the binder removal treatment in a reducing atmosphere were appropriately adjusted to be different from each other.
[0080] [Comparative Example 1]
[0081] The piezoelectric element of Comparative Example 1 was produced in the same manner as in Example 7, except that the particle size of the subphase prebaked product was set larger than that of Example 7 and the sintering temperature of the molded body after the binder removal treatment in a reducing atmosphere was set higher than that of Example 7.
[0082] [Comparative Example 2]
[0083] The same main phase prebaked product as in Example 1 was prepared. The sub-phase prebaked product was prepared by the following method. As raw material powders, Li2CO3 powder and TiO2 powder were prepared, and these raw material powders were weighed in a manner to obtain the composition (LiTi2O4) shown in Table 3. The sub-phase prebaked product was prepared in the same manner as in Example 1. Using these main phase prebaked products and sub-phase prebaked products, the piezoelectric element of Comparative Example 2 was prepared in the same manner as in Example 1.
[0084] [Comparative Example 3]
[0085] The same main phase prebaked product as in Example 1 was prepared. The sub-phase prebaked product was prepared by the following method. As raw material powders, Li2CO3 powder, Fe2O3 powder, MgO powder, and TiO2 powder were prepared, and each of these raw material powders was weighed in a manner to obtain the composition (LiFeMgTiO4) shown in Table 3. Except for this, the sub-phase prebaked product was prepared in the same manner as in Example 1. Using these main phase prebaked products and sub-phase prebaked products, the piezoelectric element of Comparative Example 3 was prepared in the same manner as in Example 1.
[0086] 〔Piezoelectric constant d 33 〕
[0087] For each piezoelectric element (piezoelectric layer) of Example 3, Comparative Example 2, and Comparative Example 3, d 33 The piezoelectric constant (pC / N) was measured using a piezoelectric meter (product name "ZJ-4B", manufactured by the Institute of Vocal Music, Chinese Academy of Sciences).
[0088] 〔Dielectric breakdown voltage〕
[0089] For each voltage element of each embodiment and each comparative example, the dielectric breakdown voltage (kV / mm) was measured according to the method shown below. With the voltage element placed in silicone oil at 25°C, a DC voltage was applied at 1 kV / mm for 1 minute, and then a DC voltage was applied for 1 minute each while the applied voltage was increased by 1 kV / mm. Then, the applied voltage (kV / mm) when the voltage element was broken down was taken as the dielectric breakdown voltage (insulation breakdown electric field) of the voltage element. The results are shown in Tables 2 and 3.
[0090] [Analysis of the main aspect]
[0091] For each voltage element (piezoelectric layer) of each example and each comparative example, using an electron probe microanalyzer (EPMA), the composition analysis of the main phase was carried out by the method shown below. The piezoelectric layer of the piezoelectric element was cut along the thickness direction, and the cut surface was polished. Then, for this polished surface, using EPMA, it was photographed at a magnification of 5000 times. From the obtained image, three points of arbitrary crystal grains in the main phase were selected, and quantitative analysis was performed on the crystal grains at these three points. Then, the average value of the content of each element in the crystal grains at these three points was used as the content (mol%) of each element in the main phase. The results are shown in Table 1.
[0092] 〔Analysis of secondary phase〕
[0093] For each voltage element (piezoelectric layer) of each example and each comparative example, using EPMA, the qualitative analysis of the secondary phase was carried out by the method shown below. For each example, the polished surface of the electric layer used in the analysis of the main phase was photographed at a magnification of 5000 times, and element mapping of Mn (manganese) and Ti (titanium) was performed using the obtained image. Then, from the obtained element mapping image, it was confirmed that Mn and Ti were present in the secondary phase. It should be noted that for Comparative Example 2, while performing element mapping of Li (lithium), Fe (iron), Mg (magnesium) and Ti (titanium), it was confirmed from the obtained element mapping image that Li, Fe, Mg and Ti were present in the secondary phase. In addition, for Comparative Example 3, while performing element mapping of Mn (manganese) and Ti (titanium), it was confirmed from the obtained element mapping image that Mn and Ti were present in the secondary phase.
[0094] In addition, for the aforementioned polished surface of each example and each comparative example, using powder X-ray diffraction (XRD: X-ray diffraction), the composition of the compound contained in the secondary phase was identified. The measurement conditions of XRD are as described below.
[0095] <Measurement conditions of XRD>
[0096] Measuring device: Powder X-ray diffractometer
[0097] Range: 50.00° - 70.00°
[0098] Wavelength: 0.7 Å
[0099] 〔Particle size (maximum particle size, average particle size, D80) of crystal grains of secondary phase〕
[0100] The above-mentioned polished surface of each embodiment and each comparative example is photographed at a magnification of 1000 times or 10000 times using a scanning electron microscope (SEM), and a measurement range of a square with a side of 250 μm is set for the obtained SEM image (reflected electron image). Then, for the multiple crystal particles existing in the measurement range, the long axis diameter and the short axis diameter are respectively calculated using image analysis software. The long axis diameter and the short axis diameter in the crystal particles are orthogonal to each other, and the long axis diameter and the short axis diameter are respectively set as the maximum values in each axis. Then, for each crystal particle, the average value of the long axis diameter and the short axis diameter is respectively used as the particle size (particle size) of each crystal particle. The average value of the particle size of each crystal particle in the above-mentioned measurement range calculated in this way is used as the average particle size (μm) of the crystal particles of the secondary phase.
[0101] It should be noted that the magnification of the SEM image was first performed at 1000 times. Then, when each crystal particle could not be identified by the obtained SEM image, the magnification was changed to 10000 times. As a result, only Example 1 took the SEM image at a magnification of 10000 times, and in other cases, the SEM image was taken at a magnification of 1000 times.
[0102] The maximum value of the major axis diameter of each crystal particle within the above measurement range was defined as the maximum particle size (μm) of the crystal particles of the subphase.
[0103] In addition, a particle size distribution was prepared for each crystal particle within the measurement range, in which the particles were arranged in order from the smallest particle size, and the cumulative 80% particle size (D80) based on the number of particles was determined for the particle size distribution. The results are shown in Tables 2 and 3.
[0104] [Table 1]
[0105]
[0106] [Table 2]
[0107]
[0108] [Table 3]
[0109]
[0110] As shown in Table 2, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 1 to 7 has a subphase formed of MnTi2O4 (Mn-Ti-O oxide). In Examples 1 to 7, the maximum particle size of the crystal particles in the subphase is 35 μm or less, and the cumulative 80% particle size (D80) based on the number of particles is 32 μm or less. The dielectric breakdown voltage of Examples 1 to 7 is 16 kV / mm or more, confirming excellent insulation properties.
[0111] In addition, as shown in Table 3, based on the measurement results of the piezoelectric constant of Example 3 which was performed as a representative example, it was confirmed that the lead-free piezoelectric composition used in the piezoelectric element of Example 3 and the like had excellent piezoelectric characteristics.
[0112] Comparative Example 1 is a case where, although it has a subphase formed of MnTi2O4 (Mn-Ti-O oxide), the maximum particle size (29 μm) of the crystal particles in the subphase and the cumulative 80% particle size (D80) (37 μm) based on the number of particles are both too large. In this Comparative Example 1, the dielectric breakdown voltage is 13 kV / mm, confirming that the insulation is low.
[0113] In addition, Comparative Example 2 is a case where a compound (LiTi2O4) containing Ti (titanium) but not Mn (manganese) is included as a subphase. Comparative Example 2 has excellent piezoelectric properties as in Example 3, but the dielectric breakdown voltage is 10 kV / mm, confirming low insulation.
[0114] Comparative Example 3 is a case of a compound (LiFeMgTiO4) containing Ti (titanium) but not Mn (manganese) as a subphase. Comparative Example 3, like Example 3, has excellent piezoelectric properties, but the dielectric breakdown voltage is 12 kV / mm, confirming low insulation.
[0115] [Examples 8 to 10]
[0116] Prepare the same main phase prebaked product as in Example 1. The sub-phase prebaked product is prepared by the following method. As raw material powders, prepare MnCO3 powder and TiO2 powder, and weigh these raw material powders in a manner to obtain the composition (Mn2TiO4) shown in Table 2. Add an appropriate amount of ethanol to the mixture of the weighed raw material powders, use a ball mill, and perform wet mixing for 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is prebaked for 1 to 10 hours under an atmospheric atmosphere at a temperature of 600 to 1100°C to obtain a sub-phase prebaked product. While using these main phase prebaked products and sub-phase prebaked products, the piezoelectric elements of Examples 8 to 10 are prepared in the same manner as in Example 1.
[0117] For each piezoelectric element of Examples 8 to 10, the main phase analysis, the sub-phase analysis, the dielectric breakdown voltage (kV / mm) were measured in the same manner as in Example 1, and the particle size (maximum particle size, average particle size, D80) of the crystal particles of the sub-phase was measured. The results are shown in Table 4.
[0118] [Table 4]
[0119]
[0120] As shown in Table 4, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 8 to 10 has a subphase formed of Mn2TiO4 (Mn-Ti-O oxide). In Examples 8 to 10, the maximum particle size of the crystal particles in the subphase is 35 μm or less, and the cumulative 80% particle size (D80) based on the number of particles is 32 μm or less. The dielectric breakdown voltage of Examples 8 to 10 is 16 kV / mm or more, confirming excellent insulation properties.
[0121] Description of Reference Numerals
[0122] 10, 200... piezoelectric element, 11, 100... piezoelectric layer (piezoelectric ceramic layer), 12, 13... internal electrode, 14, 15... external electrode, 301, 302... electrode.
Claims
1. A lead-free piezoelectric composition comprising: A main phase comprising an alkali niobate perovskite-type oxide, and A subphase containing a Mn-Ti-O-based oxide, The maximum grain size of the Mn—Ti—O-based oxide in the subphase is 35 μm or less, and the number-based cumulative 80% grain size (D80) is 32 μm or less.
2. The lead-free piezoelectric composition according to claim 1, wherein: The average particle size of the Mn—Ti—O-based oxide in the subphase is 24 μm or less.
3. The lead-free piezoelectric composition according to claim 1 or claim 2, wherein: The Mn—Ti—O series oxide includes MnTi2O4 or Mn2TiO4. 4 . A piezoelectric element comprising a laminate of a piezoelectric ceramic layer formed of the lead-free piezoelectric composition according to claim 1 or 2 and an electrode mounted on the piezoelectric ceramic layer.
Citation Information
Patent Citations
Dielectric porcelain composition
JP1982015309A
Lead-free piezo-electric porcelain composition, piezo-electric element using the same, and method for producing lead-free piezo-electric porcelain composition
CN104973863A
Unleaded piezoelectric ceramic composition, piezoelectric element using same, device, and method for manufacturing unleaded piezoelectric ceramic composition
CN105102398A
Leadless piezoelectric ceramic composition, and piezoelectric element
JP2019048749A
Lead-free piezoelectric ceramic composition, piezoelectric element, multilayered piezoelectric element, and device
JP2026008108A